FAKTOR FAKTOR YANG MEMPENGARUHI PADA PASIEN GERIATRI DENGAN STROKE ISKEMIK DI RS BHAYANGKARA ANTON SOEDJARWO PONTIANAK - Annafiatuzakiah, Annafiatuzakiah; Fita Rahmawati (Bajang Institute, 2025)
Ischemic stroke occurs when the arteries of the brain are blocked so that blood flow is reduced to the brain. Ischemic stroke requires long treatment and the use of multiple drug regimens so that there is the potential for Drug Related Problems (DRPs), unexpected events related to drug therapy that can interfere with the success of the healing process. This study aims to identify the causes of DRPs in geriatric patients diagnosed with ischemic stroke. This study used observational crosssectional design. Data collection was carried out retrospectively through medical records in 2020 at the Bhayangkara Anton Soedjarwo Hospital, Pontianak City. A total of 94 patients met the inclusion criteria including patients with a diagnosis of ischemic stroke aged 60 years or older and complete medical records. Data collection method using questionnaires and analyzed bivariately using Chi Square. The results of the study showed a relationship between risk factors age and LOS (length of Stay) with the occurrence of DRPs. At age has a p value = 0.041 and LOS has a p value = 0.031 the value is <0.05, the test using chi square confidence level used 5% with OR and CI values respectively of 2.489 (1.043-5.937) and 0.456 (0.254-0.820).